AVAILABILITY AND UTILIZATION OF MULTIMEDIA PROJECTORS IN TEACHING OF COMPUTER SCIENCE IN SENIOR SECONDARY SCHOOLS IN NNEWI METROPOLIS - Umeozor, Uzonna Juliana; Onuh, Uchenna Becky (UNIZIK Journal of Educational Management and Policy, 2024)
This study investigated the availability and utilization of multimedia projectors in the senior secondary schools in Nnewi metropolis. Two research questions guided the study. A descriptive survey research design was adopted in the study. Population for the study comprised 8 principals, 16 vice principals and 19 computer teachers from pubic senior secondary schools in Nnewi metropolis. All the participants constituted the sample size for this study making a total of 43 participants from the 8 public senior secondary schools in Nnewi metropolis using the purposive sampling technique. Two research instruments were used to conduct this study. The first instrument was a checklist containing 14 items and titled: “Availability of Multimedia Projectors in Teaching and Learning of Computer Science Questionnaire (AMPTLCSQ)”. The second research instrument was a 14-item researchers-developed questionnaire titled: “Utilization of Multimedia Projectors in Teaching and Learning of Computer Science Questionnaire (UMPTLCSQ)”.Construction of the research instruments was guided by the purpose of the study and research questions. Both face validity and reliability of the research instruments were established. Method of collection was through direct observation using the checklist in order to examine the availability of the multimedia projectors. And also a personal hand delivery and on-the-spot method was used to retrieve information from the respondents concerning the utilization of the multimedia projectors in teaching and learning of computer science in the senior secondary schools in Nnewi metropolis. Data were analyzed using different statistical tools such as the frequency, simple percentages, aggregate mean statistics rated at 2.50 and standard deviation statistics. Findings of the study revealed among others that the multimedia projectors were neither available nor utilized in teaching and learning of computer science in majority of the senior secondary schools in Nnewi metropolis. Based on the findings of the study, recommendations were made and among them include that the Anambra State Government in collaboration with the Post Primary School Service Commission (PPSSC) and incorporation with the private sector should provide the necessary multimedia projectors required in teaching and learning of computer science in the senior secondary schools in Nnewi metropolis through adequate funding, financial assistance, multimedia resources donations and facility mobilization (provision).